2006
DOI: 10.1186/1476-072x-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of campylobacter infection in the Canadian province of Manitoba

Abstract: Background: The study describes population level variations in campylobacter incidence within the Canadian province of Manitoba, and the relationship to sociodemographic and landscape related characteristics. Using data derived from the Manitoba Health Public Health Branch communicable disease surveillance database, the study applied a number of spatial and ecological techniques to visualize, explore and model campylobacter incidence for the years 1996 to 2004. Analytical techniques used in the study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 33 publications
0
47
1
1
Order By: Relevance
“…Previous studies also found no correlation between A. butzleri infection and patient age or sex (41,46). In comparison, host infection by pathogenic campylobacters is influenced by both age and sex (46,52,53), as is infection by other emerging pathogens, such as Helicobacter pylori (46) and Torque teno virus (51). We found no correlation between A. butzleri infection and place of habitation (i.e., whether patients lived in an urban or rural area).…”
Section: Discussioncontrasting
confidence: 45%
“…Previous studies also found no correlation between A. butzleri infection and patient age or sex (41,46). In comparison, host infection by pathogenic campylobacters is influenced by both age and sex (46,52,53), as is infection by other emerging pathogens, such as Helicobacter pylori (46) and Torque teno virus (51). We found no correlation between A. butzleri infection and place of habitation (i.e., whether patients lived in an urban or rural area).…”
Section: Discussioncontrasting
confidence: 45%
“…Of these, four examined the impact of SES using a composite deprivation index that incorporated area-level measures of variables such as car ownership, home ownership, and unemployment taken from national censuses (2225). Of the remaining two studies, Simonsen, et al in Denmark found an increased incidence of campylobacteriosis in persons with higher income and higher educational level (26).…”
Section: Resultsmentioning
confidence: 99%
“…The four studies of campylobacteriosis and one study of salmonellosis that used an index of deprivation to measure SES uniformly found an association between low levels of deprivation and high incidence (2225, 35). The one study of listeriosis that used an index of deprivation found an association between high levels of deprivation and high incidence (33).…”
Section: Resultsmentioning
confidence: 99%
“…Residents or workers on farms or living in proximity to high densities of farm animals, including cows, pigs, and chickens, or in rural and agricultural areas have a higher incidence of campylobacteriosis than do rural non-farm or urban residents in Canada, indicating the potential risk of campylobacters in animals to human health (Thompson et al 1986;Ellis et al 1995;Green et al 2006;Lévesque et al 2013). …”
Section: Farmed Speciesmentioning
confidence: 97%